2021
DOI: 10.1186/s13046-021-01854-5
|View full text |Cite
|
Sign up to set email alerts
|

LINC00680 enhances hepatocellular carcinoma stemness behavior and chemoresistance by sponging miR-568 to upregulate AKT3

Abstract: Background Hepatocellular carcinoma (HCC) has an extremely poor prognosis due to the development of chemoresistance, coupled with inherently increased stemness properties. Long non-coding RNAs (LncRNAs) are key regulators for tumor cell stemness and chemosensitivity. Currently the relevance between LINC00680 and tumor progression was still largely unknown, with only one study showing its significance in glioblastoma. The study herein was aimed at identifying the role of LINC00680 in the regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…found that PVT1 promotes gemcitabine resistance in pancreatic cancer by activating the Wnt/ÎČ-catenin and autophagy pathways by modulating the miR-619-5p/Pygo2 and miR-619-5p/ATG14 axes ( 12 ). In addition, LINC00680 promotes hepatocellular carcinoma stemness properties and decreases chemosensitivity by sponging miR-568 to activate AKT3 expression ( 13 ). Our previous studies and others also revealed that lncRNAs play critical roles in the chemoresistance of PCa, including HOTAIR, NEAT1, DANCR, MALAT1 and CASC2 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…found that PVT1 promotes gemcitabine resistance in pancreatic cancer by activating the Wnt/ÎČ-catenin and autophagy pathways by modulating the miR-619-5p/Pygo2 and miR-619-5p/ATG14 axes ( 12 ). In addition, LINC00680 promotes hepatocellular carcinoma stemness properties and decreases chemosensitivity by sponging miR-568 to activate AKT3 expression ( 13 ). Our previous studies and others also revealed that lncRNAs play critical roles in the chemoresistance of PCa, including HOTAIR, NEAT1, DANCR, MALAT1 and CASC2 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from cell proliferation assay revealed that knockdown of LINC00680 had the most dramatic effects on cell proliferation. Previous studies have demonstrated the oncogenic role of LINC00680 in lung cancer [ 21 , 22 ], hepatocellular carcinoma [ 23 ] and glioblastoma [ 24 ], but the functions, molecular mechanisms, and clinical relevance of LINC00680 in ESCC remains largely unknown. In the present study, we demonstrated that LINC00680 acts as an oncogenic lncRNA, which is significantly enriched in ESCC tumor tissues compared to the adjacent normal epithelial tissues, related with tumor size, depth of invasion, lymph node metastasis, and TNM stage, and predicted worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that LINC00680 regulates PAK6 expression by competitively binding to miR-423-5p, and accelerates tumorigenesis of ESCC cells. It should also be noted that LINC00680 can also sponge miR-568 to upregulate the expression of AKT3 in hepatocellular carcinoma to enhance carcinogenetic stemness behavior and chemoresistance [ 23 ]. Therefore, the potential of LINC00680 as a prognostic biomarker and therapeutic target in lncRNA-based cancer therapy warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that KDR can serve as an independent prognostic biomarker in patients with unresectable HCC (21). AKT3 is an adverse prognostic factor in patients with HCC (22), and activation of AKT3 promotes HCC stem cell properties and reduces chemosensitivity (23). In addition, KIAA1429 is significantly overexpressed in HCC tissues and is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%